Targeting cellular cathepsins inhibits hepatitis E virus entry - Klöhn, Mara; Burkard, Thomas; Janzen, Juliana; Haase, Jil A.; Gömer, André; Fu, Rebecca Menhua; Ssebyatika, George; Nocke, Maximilian K.; Brown, Richard J. P.; Krey, Thomas; Dao Thi, Viet Loan; Kinast, Volker; et al. (Hepatology, 2024)
Background and Aims: - HEV is estimated to be responsible for 70,000 deaths annually, yet therapy options remain limited. In the pursuit of effective antiviral therapies, targeting viral entry holds promise and has proven effective for other viruses. However, the precise mechanisms and host factors required during HEV entry remain unclear. Cellular proteases have emerged as host factors required for viral surface protein activation and productive cell entry by many viruses. Hence, we investigated the functional requirement and therapeutic potential of cellular protease during HEV infection. - Approach and Results: - Using our established HEV cell culture model and subgenomic HEV replicons, we found that blocking lysosomal cathepsins (CTS) with small molecule inhibitors impedes HEV infection without affecting replication. Most importantly, the pan-cathepsin inhibitor K11777 suppressed HEV infections with an EC50 of ~0.02 nM. Inhibition by K11777, devoid of notable toxicity in hepatoma cells, was also observed in HepaRG and primary human hepatocytes. Furthermore, through time-of-addition and RNAscope experiments, we confirmed that HEV entry is blocked by inhibition of cathepsins. Cathepsin L (CTSL) knockout cells were less permissive to HEV, suggesting that CTSL is critical for HEV infection. Finally, we observed cleavage of the glycosylated ORF2 protein and virus particles by recombinant CTSL. - Conclusions: - In summary, our study highlights the pivotal role of lysosomal cathepsins, especially CTSL, in the HEV entry process. The profound anti-HEV efficacy of the pan-cathepsin inhibitor K11777, especially with its notable safety profile in primary cells, further underscores its potential as a therapeutic candidate.
Gesehen am 26.11.2024